Cervical Cancer Awareness: An Information Dissemination Campaign In Indonesia - Dedeh Sri Rahayu; Sri Rahayu; Marcos Ochoa (Universitas Padjadjaran, 2017)
This descriptive-correlational study was conducted to determine the level of cervical cancer awareness of 196 participants who were conveniently recruited from selected regions in South Cimahi, Melong, West Java,Indonesia. The survey was conducted on February 2014 for fifteen (15) days using a survey questionnaire for data collection. Descriptive statistics such as frequency and percentage distribution were used for demographic profile and weighted mean for the assessment of the level of awareness on cervical cancer, and inferential statistics such as Pearson r and chi square for hypothesis testing. They have moderate awareness on basic information on cervical cancer, foremost are the areas on prevention, anatomy, treatment and common diagnostic examination, but with very little knowledge or partial awareness on the items pertaining to signs and symptoms, etiology and mode of transmission of cervical cancer. The results of chi square and pearson r tests found that the participants' gender and educational attainment were not significantly correlated with their level of awareness on cervical cancer while, family monthly income was significantly correlated to their level of awareness. Hence, this study concluded that gender and educational attainment do not necessarily determine a person's level of awareness or knowledge but family income could contribute to their level of awareness. The study findings formed the basis of designing an information dissemination campaign material on cervical cancer among the residents of South Cimahi, Indonesia. In this regard, an intensive information dissemination campaign program on cervical cancer is recommended using the proposed campaign material designed.